Esophageal achalasia, an unexpected complication of COVID-19 post palatoplasty: a case report and literature review - Njokanma, Azuka R.; Aborisade, Adetayo; Ojo, Olugbenga O.; Adeyemi, Adewale C.; Njokanma, Ada H.; Adumah, Collins C. (International Journal Of Community Medicine And Public Health, 2024)
The COVID-19 pandemic, caused by SARS-COV-2, has led to significant mortality worldwide. Despite the declaration in May, 2023 by the World Health Organization (WHO), that the COVID-19 pandemic in no longer a public health emergency of international concern, some survivors are experiencing post-infection complications, including esophageal achalasia. Esophageal achalasia is a rare neurodegenerative disorder characterized by impaired esophageal motility and lower esophageal sphincter dysfunction. This study reviews the literature to explore the association between COVID-19 and achalasia and also presents a case of a 9-month-old child diagnosed with achalasia following COVID-19 infection; a unique occurrence in a young child. This study comprises a case report and a literature review. Clinical data for the case report was collected from medical records, while the literature review included a search of electronic databases from January 2020 to October 2023. Keywords related to COVID-19 and esophageal achalasia were utilized to conduct a search in electronic databases resulting in 9 selected articles. This study underscores the emerging concern of esophageal achalasia as a post-infection complication of COVID-19. It provides a unique case of a young child developing achalasia after COVID-19 infection and reviews the limited literature on this association. Further research is needed to understand the underlying mechanisms and potential preventative measures for this rare complication in COVID-19 survivors.